Hippocampal Subfields in Mild Cognitive Impairment: Associations with Objective and Informant-Report of Memory Function. (19th April 2022) - O'Shea, Deirdre M; de Wit, Liselotte; Tanner, Jared; Mejia Kurasz, Andrea; Amofa, Priscilla; Perez Lao, Ambar; Levy, Shellie-Anne; Chandler, Melanie; Smith, Glenn
Abstract: Background: Evidence suggests that select hippocampal subfields are implicated in the initial stages of Alzheimer's disease (AD) and are selectively involved in objective memory. Less is known whether subfields are associated with informant-reported memory difficulties of individuals with a diagnosis of mild cognitive impairment (MCI). Method: Data from 56 participants with a diagnosis of amnestic MCI were included in the present study. To test whether FreeSurfer derived hippocampal subfields (CA1–4, subiculum, presubiculum, and dentate gyrus) were associated with objective (learning and delayed recall) and informant-reports of memory difficulties, we used multiple linear regression analysis. Subfields were adjusted for total intracranial volume, and age, sex, and years of education were included as covariates in all models. Results: Larger presubiculum, subiculum, and CA4/dentate gyrus volumes were associated with higher delayed recall scores, and larger subiculum and CA4/dentate gyrus volumes were associated with fewer informant-reports of memory difficulties. There were no statistically significant associations between subfields and learning scores. Discussion: Findings from the present study support the idea that difficulties with memory-dependent everyday tasks in older adults with MCI may signal a neurodegenerative process while increasing understanding of subfields correlates of these memory-specific functional difficulties. Continued investigations into identifying patterns of subfield atrophy in AD may aid early identification of those at higher risk of dementia conversion while advancing precision medicine.